Post-exodontic bone regeneration due to dental fracture of traumatic origin - Alcázar-Aguilar, Oscar O. (2022)
The present article aims to report a clinical case that exposes the guided bone regeneration treatment (ROG) in a tooth with a traumatic fracture. The procedure consisted of bone regeneration, which has proven to be a successful technique to promote the recovery of dentoalveolar bone defects. Lyophilized organic bovine bone and resorbable bovine collagen membrane were placed one month after having suffered a dentoalveolar trauma at the level of the upper right central incisor. In conclusion, the treatment proved to be very effective in increasing and preserving the dimensions of the resorbed alveolar ridges, optimizing the biological conditions of our patients for subsequent rehabilitation.